2012
DOI: 10.1007/s11743-012-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of CMC Evaluation in Single and Mixed Surfactant Systems, Using the UV–Vis Spectroscopic Method

Abstract: In this study, the critical micellar concentration (CMC) of anionic, cationic and nonionic surfactants was determined using the UV-Vis spectroscopic method. Sodium lauryl sulfate (SDS) as anionic, hexadecyl-trimethyl-ammonium bromide as cationic, tert-octylphenol ethoxylates TOPEON (with N = 9.5, 7.5 and 35) and lauryl alcohol ethoxylate (23EO) as nonionic surfactants have been used. Concentration of surfactants varies both from below and above the CMC value in the pyrene solution. In addition, the amount of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The spectra with varying concentration of surfactant yield important information regarding the interaction between pyrene and surfactant. The simple UV-Vis absorbance spectrum of pyrene in water gives four strong peaks at 242, 272, 320, and 336 nm due to multiple rings [36]. The total absorbance (A T ) i.e.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
“…The spectra with varying concentration of surfactant yield important information regarding the interaction between pyrene and surfactant. The simple UV-Vis absorbance spectrum of pyrene in water gives four strong peaks at 242, 272, 320, and 336 nm due to multiple rings [36]. The total absorbance (A T ) i.e.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
“…The fluorescence emission spectrum of pyrene exhibits five characteristic bands in the region 370-400 nm. The polarity of the microenvironment around the pyrene molecules is related to the ratio of the intensities of the first to third major vibrational peaks (I 1 /I 3 ) and lower value of I 1 /I 3 indicates apolar environment [50,51]. Pyrene molecules get distributed into micelles as soon as they form and this process is accompanied by an abrupt decrease in the I 1 /I 3 ratio indicating the micellization process, when a surfactant is added to an aqueous solution containing pyrene.…”
Section: Fluorescence Probe Studiesmentioning
confidence: 99%
“…The absorption spectrum of pyrene has evidenced eight strong (s) and weak (w) peaks (232 w, 242 s, 252 w, 260 w, 272 s, 308 w, 320 s, and 336 s nm). It is reported that the absorbance at 242 nm increases with the polarity of the solvent, while above 315 nm, absorbance decreases with the solvent polarity [51,52]. Since there is no hydrophilic functionality of pyrene, the absorbance of the pyrene peaks enhances with increase in concentration of surfactants.…”
Section: Uv-vis Probe Studiesmentioning
confidence: 99%
“…The small increase in the absorbance at low surfactant concentration (pre‐micellar region) suggests tendency of pyrene to stay in polar environment of water molecules and low solubilization of pyrene. However at CMC, the abrupt increase in the absorbance shows migration of hydrophobic pyrene into hydrophobic environment of micelles and its high solubility (Tanhaei et al, 2013). The higher A T values of drug‐surfactant system as compared to aqueous surfactant systems put ahead the supremacy of hydrophobic interactions in the former.…”
Section: Resultsmentioning
confidence: 99%